Light intensity can trigger different agonistic responses in juveniles of three cichlid species - Carvalho, Thais B.; Ha, James C.; Goncalves-de-Freitas, Eliane [UNESP] (Taylor & Francis Ltd, 2012)
Light intensity affects aggressive behavior in fish because this variable influences physiological processes. Such effects could, however, vary according to the species and the ontogenetic stage of life because different life history can modulate behavior. Thus, we compared the effect of light intensity on the agonistic behavior of juvenile cichlids acara tinga Geophagus proximus, Nile tilapia Oreochromis niloticus, and the angelfish Pterophyllum scalare under low and high light intensity conditions. Fish were isolated in 36 l-aquaria for 96 h and paired (resident-intruder) until hierarchy settlement, while agonistic interactions were recorded. High light intensity increased latency to fighting in G. proximus and O. niloticus, but did not affect it in P. scalare. High light intensity also affected the occurrence of several other agonistic behaviors (chase, circling, lateral fight, frontal display, and mouth fight) but in different ways across the three species. We conclude that mechanisms underlying these data reflect differences in the natural history of the cichlid species.
Keywords: aggressiveness; rank order; environmental disturbance; life history